Analisis Situasi Kampus Mengajar di SD Negeri Tanjungrejo 06 Dalam Program Merdeka Belajar Kampus Merdeka - Belva Yulvia Doviani; Shaya Seriefaza; Astri Widyaruli Anggareni (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of the Teaching Campus activity program for students at the Faculty of Teacher Training and Education is as a means for students to prepare themselves to become quality educators, and also to create the identity of an educator as well as to increase their knowledge about education. What will be done in carrying out the Teaching Campus program activities are debriefing, observing the school environment, observing learning in class and activities for forming work programs. The school situation certainly has many obstacles in educating its students. Therefore, prospective educators must be able to understand, and also find and search for various solutions to problems that have been observed in various ways which are of course fast and accurate. The situations we find in school and in learning often result in discrepancies from the learning plans expected by an educator. Therefore, an educator has other ways to carry out learning so that learning can be said to be successful and according to plan. Therefore, it is necessary to be close to students as a way for us to know the nature and characteristics of each student so that it can help to overcome problems that exist when learning takes place. When finding problems, prospective educators create ways to minimize various obstacles by using various learning methods which include interactive, active and interesting methods which aim to motivate students so that they are active in the classroom. Apart from these methods, prospective educators must teach various materials which are of course relevant to students' daily lives.